Non-destructive integrity assessment of aging steel components. (August 2022) - Bolzon, Gabriella; Talassi, Marco
Abstract: This contribution addresses the integrity assessment of steel components in operation by introducing a simple non-destructive investigation technique. The proposed methodology is based on superficial (according to ASTM E18 Standards classification) hardness tests, complemented by the mapping of the geometry of the residual imprint. The diagnostic analysis can be performed in situ, potentially in a fully automated way. The informative content of the collected data is verified on the results of previous laboratory studies. The proposed material characterization procedure is applied to determine the evolution over the years of the mechanical properties of an exercised gas pipeline. Highlights: A non-destructive diagnostic technique is introduced for exercised metal components. The methodology is based on the mapping of residual imprints left by hardness tests. Few kN applied load reduces encumbrance of portable instruments and mapping times. The proposal is verified against truly experimental data concerning pipeline steel.